Compaction and clay content control mudrock porosity - Rezaeyan, Amirsaman; Kampman, Niko; Pipich, Vitaliy; Barnsley, Lester C.; Rother, Gernot; Magill, Clayton; Ma, Jingsheng; Busch, Andreas (Energy (Oxford), 2024)
Mudrocks, ubiquitous yet poorly understood sedimentary rocks with significant variations in composition and physical properties, form seals for geological carbon dioxide and energy (e.g., hydrogen and methane) storage, repositories for radioactive waste disposal, and reservoirs for natural gas. Understanding the controls on mudrock pore structure is essential for evaluating their porosity. The identification and quantification of controls depend on the nano-to micron scale pore network, which are the subject of this study. Small-angle (SANS) and very small-angle neutron scattering (VSANS) experiments were conducted on 13 diverse mudrock sets, characterised by differences in mineralogy, stratigraphy, maturity, and depositional environment. We performed multivariate statistics to systematically characterise the pore structure in 71 samples cross a 5 μm–2 nm pore size range. Our results indicate a multivariate approach more effectively captures the complex controls on porosity rather than single parameters. Compaction and clay content emerge as key primary and secondary controls on mudrock porosity, respectively, upon which we introduce a new porosity classification. Our complementary experimental-statistical assessment involving SANS-derived multiscale porosity sheds new light on the influence of structural controls on storage or production capacity in mudrocks. [Display omitted] •Compaction is the primary and clay the secondary control on mudrock porosity.•While TOC barely affects mudrock porosity, it influences meso/macropores the most.•Mudrock controls influence porosity across various scales.